Escherichia coli: ANTIMICROBIAL SUSCEPTIBILITY MONITORING 2015 – 2018 IN BRAZIL - Levandowski, Rafael (2019)
Commensal bacteria, such as Escherichia coli, are involved in the transmission of resistance genes because it is widely distributed and constantly exposed to antibiotics. In this study, we examined multidrug resistance (MDR) in 282 collections of Escherichia coliisolates recovered from hospitalized animals in Brazil. A total of 2186 disc diffusion susceptibility tests were performed for 22 antibiotics. We verified 100% resistance for Lincomycin, metronidazole and penicillin and for other drugs we observed: sulfonamide (77%), amoxicillin (75%), cephalothin (70%), ampicillin (57%), tetracycline (52%), doxycycline (48%), amoxicillin plus clavulanic acid (47%), cephalexin (45%), sulfamethoxazole plus trimethoprim (41%), ciprofloxacin (40%), cefazolin (40%), trimethoprim (39%), norfloxacin (34%), enrofloxacin (34%), neomycin (33%), florfenicol (27%), ceftiofur (24%), chloramphenicol (20%) and gentamicin (17%). In addition, multidrug resistance was observed in 39% (151/282) of the samples tested. The study demonstrated that E. coli isolates showed resistance to antibiotics used in human medicine and, due to the ability to transfer resistance genes, is a public health issue. Multidrug resistance limits the drug choice for the treatment of E. coliinfections, suggesting that veterinarians seek antimicrobial alternatives.